Solar flares induced D-region ionospheric and geomagnetic perturbations - Selvakumaran, R.; Maurya, A. K.; Gokani, Sneha A.; Veenadhari, B.; Kumar, Sushil; Venkatesham, K.; Phanikumar, D. V.; Singh, Abhay K.; Siingh, Devendraa; Singh, Rajesh (My University, 2015)
The D-region ionospheric perturbations caused by solar flares which occurred during January 2010–February 2011, a low solar activity period of current solar cycle 24, have been examined on NWC transmitter signal (19.8 kHz) recorded at an Indian low latitude station, Allahabad (Geographic lat. 25.75°N, long. 81.85°E). A total of 41 solar flares, including 21 C-class, 19 M-class and 01 X-class, occurred during the daylight part of the NWC-Allahabad transmitter receiver great circle path. The local time dependence of solar flare effects on the change in the VLF amplitude, time delay between VLF peak amplitude and X-ray flux peak have been studied during morning, noon and evening periods of local daytime. Using the Long Wave Propagation Capability code V 2.1 the D-region reference height (H/) and sharpness factor (β) for each class of solar flare (C, M and X) have been estimated. It is found that D-region ionospheric parameters (H/, β) strongly depend on the local time of flare's occurrence and their classes. The flare time electron density estimated by using H/ and β shows maximum increase in the electron density of the order of ~80 times as compared to the normal day values. The electron density was found to increase exponentially with increase in the solar flux intensity. The solar flare effect on horizontal component (H) of the Earth's magnetic field over an equatorial station, Tirunelveli (Geographic lat., 8.7°N, long., 77.8°E, dip lat., 0.4°N), shows a maximum increase in H of ~8.5% for M class solar flares. The increase in H is due to the additional magnetic field produced by the ionospheric electrojet over the equatorial station.
Keywords: Solar flares; VLF waves; Very low frequency waves; D-region ionosphere; Ionospheric electrojet